When eight bells toll - MacLean, Alistair, 1922- (New York : Ballantine, 1983)
Agent Philip Calvert begins his pursuit of a superbly organized gang of seagoing hijackers.
"Fawcett Crest book.".
Fiction Catalog (Wilson).
Library Journal.
Adult.
Adult
Keywords: Hijacking of ships -- Fiction; Hijacking of ships -- Fiction